The perks of being a wallflower [compact disc] : original motion picture soundtrack. - Brook, Michael, 1952-; Bowie, David (Summit Entertainment Records/Chop Shop/Atlantic, 2012)
A wide variety of musical styles and artists fills the soundtrack to the big screen adaptation of Stephen Chbosky's popular novel.